DATURA METEL LINNAEUS SEBAGAI INSEKTISIDA DAN LARVASIDA BOTANI SERTA BAHAN BAKU OBAT TRADISIONAL - Mardiana, Mardiana; Supraptini, Supraptini; Aminah, Nunik Siti (Badan Penelitian dan Pengembangan Kesehatan, 2009)
Controlling dengue hemorrhagic fever vector would be better when the people could choose their own choice of method such as spraying synthetics insecticide, using abate as synthetics larvacide, using fish as biological controller, and using electrical racket as mechanical controller. Besides, using poisonous plant as alternative controlling method was being encouraged. Datura metel is a wild plant from a mountain area, which could not be eaten, easy to grow, cheap, safe and environmental friendly. Lethal concentration CL50 towards larvae is 0.600 µg, and CL 95 to control Aedes aegypti larvae is 1.250 µg. Al Using extract of